Electrodermal Activity and Chronotropism for Transient Occlusion of Major Upper Arm Artery: a Quantitative Assessment of Autonomic Response - Nepal, Ojashwi; Ray, Abhishek Ranjan; Pokhrel, Sony; Jha, Reena Kumari (Journal of College of Medical Sciences-Nepal, 2020)
Background: Blood vessels in body respond to sympathetic upsurge and, occlusion of blood vessels supplying vital organs excites autonomic reactions, building up chaos in homeostasis. Autonomic response to occlusion of major artery, not supplying to vital organs, remains least explored in the medical literature. Thus we have observed, in vivo, undulating autonomic response to heart beat and galvanic skin response for transient occlusion of left brachial artery, in this study. Methods: Occlusion of brachial artery was maintained approximately 10mmHg above the systolic pressure by mercury manometer with cuff inflated at two inches above the cubital fossa of left hand. Heart rate and skin conductance was picked up by the transducers placed at appropriate locations on body surface in 40 subjects. Results: Paired t test, repeated measures ANOVA and Pearson correlation are utilized to compare the recorded variables. Heart rate is significantly decreased (p=0.000) and amplitude of galvanic skin response is significantly increased (p=0.000) in all subjects for induced occlusion of brachial artery in left arm. ANOVA compared among levels of pre-occlusion, occlusion and post-occlusion is significant for heart rate (p=0.000). Pearson correlation between GSR and heart rate is weakly inverse (r = -0.028). Conclusions: Episodic occlusion of artery does excite the autonomic reactions in healthy young adults. Simultaneous rise in parasympathetic and sympathetic response is an obligatory autonomic response for the brief occlusion of left brachial artery.